Sustentabilidade e estratégia em empresas industriais do setor de artefatos de borracha - Vencato, Carlos Henrique da Rocha (2012)
Several changes are affecting the Earth‟s sustainability and start to change the way people perceive the organizations, bringing consequences and alterations in their organizational strategies. The current research aimed to analyze the relations between the sustainability, strategy and the process of making these rubber companies international ones. The research had two distinct phases, being the first one a qualitative and descriptive research with semi-structured interviews. The empirical concretization of this paper occurred in two huge industrial plants in Rio Grande do Sul state, one located in São Leopoldo municipality and the other in Santa Cruz do Sul municipality. Both companies are Brazilian and produce rubber products. The second stage encompassed the application of a quantitative and descriptive research where it was proposed the characterization of the company, the strategic management of sustainability, the international experience and their export performances. The statistic and descriptive data of the quantitative research were collected from the companies associated to ABIARB‟, Brazilian Association of Rubber Product Industries, to SINBORSUL‟, Union of the Rubber Industries of Rio Grande do Sul state, and to SINDIBOR‟, Union of Rubber Product Industries of São Paulo state. The results of the qualitative phase point out that the companies analyzed here search for the involvement of their providers and stakeholders in the environmental and social management, they show several internal barriers in the implementation of sustainability, make their employees aware about sustainability, try to innovate by having the sustainability as something linked to their business actions, are advanced international enterprises and use their sustainable consciousness in their strategic performances. The results from the quantitative stage show that these companies are mostly small or medium ones, with some experience in the market of light products (internationalized companies) and in the rubber industry (non-internationalized). Generally, it was possible to verify that the analyzed firms involve their stakeholders and their employees in sustainable strategies, become international due to exports, by means of intermediary workers in Brazil and are in their initial stages of internationalization. The analyzed data allowed identify the great importance of sustainability, with few barriers against their implementations. Furthermore, it is possible to say that the actions which are towards the practice of sustainability management helped positively for the export performance, confirming the hypotheses of this paper.